Yusuf Khos Khojib oriental pearl (Zien Journal of Social Sciences and Humanities, 2022)
In the article has analyzed Yusuf Khas Hajib’s «Qutadgu bilig» works and determined his role in the history of oratory and art of speech, including giving them a scientific-theoretical assessment.